2019
DOI: 10.1016/j.tree.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Is Breaking Earth’s Beat

Abstract: Forests, deserts, rivers, and oceans are filled with animal vocalizations and geological sounds. We postulate that climate change is changing the Earth's natural acoustic fabric. In particular, we identify shifts in acoustic structure that all sound-sensitive organisms, marine and terrestrial, may experience. Only upstream solutions might mitigate these acoustic changes. 1 Text From pole to pole, numerous animal species transmit sounds for communication, foraging, and navigation, in particular. Sound is a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 12 publications
2
47
0
Order By: Relevance
“…As shown here and in previous studies (Krause & Farina, 2016;Llusia, Márquez, Beltrán, Benítez, et al, 2013;Sueur et al, 2019), automated acoustic monitoring techniques (Sugai et al, 2019)…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As shown here and in previous studies (Krause & Farina, 2016;Llusia, Márquez, Beltrán, Benítez, et al, 2013;Sueur et al, 2019), automated acoustic monitoring techniques (Sugai et al, 2019)…”
Section: Discussionsupporting
confidence: 76%
“…As shown here and in previous studies (Krause & Farina, 2016; Llusia, Márquez, Beltrán, Benítez, et al, 2013; Sueur et al., 2019), automated acoustic monitoring techniques (Sugai et al., 2019) can provide important information on species behaviour under different climatic conditions, thus assisting climate change research. With these new techniques, the thermal breadth of calling activity can also be further investigated and provide a complementary view on the response capacity of anuran amphibians to climate change.…”
Section: Discussionsupporting
confidence: 72%
“…anthropogenic noise), can provide further (year-round) contextual information on the ecological and acoustic quality of underwater marine habitats. In light of on going environmental changes, the potential of passive acoustic surveys and acoustic indices in the context of biodiversity and habitat quality monitoring is still heavily underexploited (Sueur et al 2019). Particularly for the marine realm, these methods represent a source of untapped and hidden potential to become vital players for efficient large-scale environmental monitoring of the Earth's natural soundscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported significant differences among biological sounds of different habitats, which reveal a spatial heterogeneity and could serve as indicators of habitat type [25,28,29]. Other authors have postulated that climate change is shifting the sounds of our environments [30], and sounds have been proposed as a proxy to measure the effects of changes on biological populations and assemblages. A reduction in frequency and intensity of sounds produced by the world's noisiest marine invertebrate (the snapping shrimp, Alpheus sp.)…”
Section: (B) Sounds Measuring Ecosystem Functionsmentioning
confidence: 99%